2008
DOI: 10.1038/ejhg.2008.201
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability of patients homozygous for the GJB2 mutation 35delG cannot be explained by the influence of one major modifier gene

Abstract: Hereditary hearing loss (HL) is a very heterogeneous trait, with 46 gene identifications for non-syndromic HL. Mutations in GJB2 cause up to half of all cases of severe-to-profound congenital autosomal recessive non-syndromic HL, with 35delG being the most frequent mutation in Caucasians. Although a genotypephenotype correlation has been established for most GJB2 genotypes, the HL of 35delG homozygous patients is mild to profound. We hypothesise that this phenotypic variability is at least partly caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
3
31
0
3
Order By: Relevance
“…The c.35delG mutation is the main cause of early childhood onset HL in Estonian children, and accounts for 75% of GJB2 alleles. This proportion is similar to that reported in studies of other Caucasian populations as ranging between 58 and 95% [12,14,[19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…The c.35delG mutation is the main cause of early childhood onset HL in Estonian children, and accounts for 75% of GJB2 alleles. This proportion is similar to that reported in studies of other Caucasian populations as ranging between 58 and 95% [12,14,[19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…Single nucleotide polymorphisms (SNPs) may have small modifying effects on the phenotype caused by GJB2 genotypes. Hilgert and colleagues using a wholegenome association (WGA) study have suggested that the variable phenotype in 35delG homozygous patients may not be explained by one major modifier gene [25]. However, further studies are needed to identify any possible modifiers.…”
Section: Discussionmentioning
confidence: 97%
“…This phenotypic variation was explained by the influence of modifier genes and/or environmental factors that lead to incomplete penetrance and variable expression [18,19]. Other studies consider that the phenotypic variation may be caused by a smaller effect of different interacting genes [20].…”
Section: Discussionmentioning
confidence: 99%